The Truth and Certainty in Wittgenstein’s Philosophy - Plėšnys, Albinas (Problemos, 2003)
Truth can be treated from at least three viewpoints. First, truth is an ontological concept, subordinated to that ontological model to which a particular philosopher adheres. In the Aristotelian philosophical tradition, truth is a transcendental concept, expressing the relationship between being and cognition. The Aristotelian tradition describes truth as the correspondence between the thing and the intellect - veritas est adaequatio rei et intellectus. The second aspect of truth is logical. Its essence could be formulated in the following way: is it possible to use the concept of truth logically correctly and precisely in a language, characterized by an exact structure? In his famous article The Semantic Conception of Truth and the Foundations of Semantics Alfred Tarski proved that a logically irreproachable conception of truth is possible if the object language and the metalanguage are discerned. The third aspect of truth is ethical, but it is not the topic of present discussion. In his Tractatus Logico-Philosophicus Ludwig Wittgenstein proposed the ontological model by means of which he formulated the conception of truth as the correspondence of facts to reality in a logical space. The conception of truth here turns into a basis of distinguishing between what can be talked about and what should be passed over in silence. Truth is one of the major problems in Tractatus. The later Wittgenstein abandoned his ontological scheme and a related conception of exact truth. In Philosophical Investigations the central issue is the concept of the language-game. The language-game consists not only of linguistic rules and names of objects. The whole process of using words, for Wittgenstein, is a certain part of an activity and a form of life. Later Wittgenstein does not recognize any a priori instructions or rules, which would allow to determine the correctness of the proposition or the structure of the world. Having abandoned the a priori and the only ontological scheme, Wittgenstein abandons the conception of ontological truth as well, treating certainty as an internal feature of the language-game. In his opinion, subjective certainty means merely that there does not exist an alternative language-game which could raise doubts about certainty.